Palynofacies assemblages reflect sources of organic matter in New Zealand fjords. (15th February 2018) - Prebble, Joseph G.; Hinojosa, Jessica L.; Moy, Christopher M.
Abstract: Understanding sources and transport pathways of organic carbon in fjord systems is important to quantify carbon cycling in coastal settings. Provenance of surficial sediment organic carbon in Fiordland National Park (southwestern New Zealand) has previously been estimated using a range of techniques, including mixing models derived from stable isotopes and lipid biomarker distributions. Here, we present the first application of palynofacies to explore the sources of particulate organic carbon to five fjords along the SW margin of New Zealand, to further discriminate the provenance of organic carbon in the fjords. We find good correlation between isotopic-and biomarker-derived proxies for organic carbon provenance and our new palynofacies observations. We observe strong down-fjord gradients of decreasing terrestrially derived organic carbon further from the river inflow at fjord heads. Fjords with small catchments and minor fresh water inflow exhibit reversed gradients, indicating that volume of freshwater entering at the fjord head is a primary mechanism to transport particulates down fjord rather than local transport from fjord sides. The palynofacies data also confirmed previously recorded latitudinal trends (i.e. between fjords), of less frequent and more weathered terrestrially derived organic carbon in the southern fjords, consistent with enhanced marine inflow and longer transport times in the southern catchments. Dinocyst assemblages also exhibit a strong latitudinal gradient, with assemblages dominated by heterotrophic forms in the north. In addition to providing support for previous studies, this approach allows finer discrimination of terrestrial organic carbon than previously, for example variation of leaf material. This study demonstrates that visual palynofacies analysis is a valuable tool to pinpoint origins of organic carbon in fjord systems, providing different but complementary information to other proxies. Highlights: palynofacies reflect sources of particulate organic carbon to New Zealand fjords. strong correlation with isotopic-and biomarker-derived proxies for organic carbon. strong down-fjord gradients of decreasing terrestrially derived organic carbon. less terrestrial carbon in southern fjords from marine inflow and slower transport.